Formation Evaluation by using Well Logging of Mishrif Formation in the Noor Oil Field, , Southeast Iraq - Altameemi, Ali M. Hasan; Alzaidy, Aiad (Iraqi Journal of Science, 2018)
Mishrif Formation regards one of the most important reservoirs in Iraq. Well logging represents one of the most important tool in the formation evaluation. According to the Petrophysical properties that have been gotten from well logging, Mishrif Formation in terms of reservoirs units, consist of several reservoirs units. Major reservoirs units divided into three reservoir units,MA,MB&MC. Each of these major units divided into minor reservoirs units (MB11,MB12,MC2&MC3).MB major reservoir units represent the best reservoir unit. These reservoirs units separated by cap rocks(mainly tight limestone)(CR1,CR2,CR3,CR4,CR5,CR6,and CR7).CPI were demonstrated for all wells.Hydrocarbon saturation vs. water saturation have been determined for eachunits.In addition, the types porosity and moveable vs.residual oil were calculated.